METHODS OF DIAGNOSIS AND TREATMENT IN PATIENTS WITH MAXILLARY SINUS CYSTS - Jamolbek A. Djuraev; Sunnatilla A. Mirzaev; Ilyosjon O. Soatov (Central Asian Journal of Medicine, 2025)
Maxillary sinus cysts are a type of cyst located within the maxillary sinus. These cysts can arise from various causes, such as infections, injuries, or congenital defects. If cysts are not treated in a timely manner, they can damage the jaw bones and disrupt the normal functioning of teeth. In our scientific study, the total number of patients was 140. According to the WHO classification, patients were divided into 3 age groups, and all of them underwent surgery. The first group consisted of 68 patients aged 18-44 years. The second group consisted of 45 patients aged 45-59 years. The third group consisted of 27 patients aged 60-74 years.